2013
DOI: 10.1177/2049463713487895
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of pain manikins: a comparison of paper versus online questionnaires

Abstract: BackgroundIn epidemiological studies, pain location is often collected by paper questionnaire using blank body manikins, onto which participants shade the location of their pain(s). However, it is unknown how reliable these will transfer to online questionnaires. The aim of the current study was to determine agreement between online-and paper-based completion of pain manikins. Methods A total of 264 children, aged 15-18 years, completed both an online and a paper questionnaire. Participants were asked to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“… 12 However, van den Hoven et al (2010) compared musculoskeletal pain prevalence data from manikins with data from written questions and concluded that the 2 approaches yield similar findings. 16 Pain location in population-based surveys seem to be captured in a comparable fashion on manikins administrated online vs paper and pencil, 9 and pain intensity measured by visual analogue scale seems to be similarly captured across administration modes. 10 , 13 Findings indicate that the response rate is similar in paper and pencil and online surveys, but with faster available data with online administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 However, van den Hoven et al (2010) compared musculoskeletal pain prevalence data from manikins with data from written questions and concluded that the 2 approaches yield similar findings. 16 Pain location in population-based surveys seem to be captured in a comparable fashion on manikins administrated online vs paper and pencil, 9 and pain intensity measured by visual analogue scale seems to be similarly captured across administration modes. 10 , 13 Findings indicate that the response rate is similar in paper and pencil and online surveys, but with faster available data with online administration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, electronic tools seem to capture information about pain that is equivalent to paper and pencil assessments. 1 , 3 , 5 , 9 , 10 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…The interval must be sufficiently long so that the patient has no memory of the first measurement as this could influence the responses in the second session. Meanwhile, the interval should also be short enough that the underlying characteristic under investigation does not vary between the sessions [ 32 ]. Furthermore, a longer interval can reduce patient participation in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size is, according Terwee et al, 2007 [ 31 ]. We performed the tests with a 1-hour interval between the two applications [ 32 ]: original image and adapted image. The order of application was randomized, and in 50% of the participants, the original image was applied first, followed by the adapted image, but the order was reversed in the other 50%.…”
Section: Methodsmentioning
confidence: 99%
“…23 Advances in technology may have increased the diagnostic accuracy of non-linguistic representation, but use in headache is not common. [39][40][41][42] Perhaps headache as a symptom and headache patients may present other challenges not yet met, 23,43,44 though studies have suggested that the amount of area of head pain associates with neuropsychological outcomes in headache but not, for instance, mood disorders.…”
Section: Discussionmentioning
confidence: 99%